(untitled) (Herald of Journalism, 2016)
Currently, almost all developed countries of the world recognized the need to reform their education systems so that students really become the pivotal figure of the educational process and to focus on the student’s cognitive activity by educators and researchers. Modern information society puts the task of preparing graduates able to be flexible to adapt to changing situations, independently acquiring the necessary knowledge, skillfully applying them in practice for solving a variety of arising problems, to be able to find their place in it .